Method development for simultaneous determination of multi-mycotoxins in palm kernel cake - Yibadatihan, Simayi (2015)
Palm kernel cake (PKC) has been widely used for animal feed production as being a useful source of protein and energy for livestock. However, PKC can easily be contaminated with mycotoxins during production and storage owing to its favourable environments for the fungus to grow. Public concerns about the consequential economic losses and health risks for animals and humans have accentuated the need for evaluation of mycotoxins in PKC. Furthermore, a method for determination of multimycotoxins in PKC has so far not been established. The European Commission has set maximum regulatory limits of 5-50, 50-250, 100-3000, 900-12000, 5000-60000, 250- 2000 and 250-2000 ng g-1 for aflatoxin B1, ochratoxin A, zearalenone, deoxynivalenol,fumonisins, T-2 and HT-2 toxins, respectively intended for animal feeds. This research was therefore conducted to develop an LC-MS/MS method for simultaneous determination of the 11 mycotoxins (aflatoxins B2, G1, G2 and the regulated mycotoxins) in PKC. The LC-MS/MS method was developed through the investigation of different ionization process, collision energies, and different types of mobile phase. Then, the LC-MS/MS detection conditions including flow rate (0.15-0.3 ml min-1), acid percentage in the mobile phase (0-0.7%), organic percentage at the beginning (5-25%) and at the end (70-90%) of the gradient mobile phase were optimized using central composite design (CCD). The best detection and separation of all the target mycotoxins were achieved using electro spray ionization (ESI) in both positive and negative ionmodes under the optimized LC-MS/MS detection parameters, which were 10% methanol at the beginning and 90% at the end of the gradient mobile phase with 0.2% formic acid and at the flow rate of 0.2 ml min-1. The efficiency of different ratios of extraction solvents composed of acetonitrile or methanol with water (50:50-90:10, v:v) was also investigated, followed by the evaluation of formic acid (0.1-2%) effect on the recovery of mycotoxins. Purification approaches of no clean-up and clean-up with immunoaffinity column (IAC) were also compared. The highest recovery of target mycotoxins (88-110%) were obtained by using acetonitrile:water:formic acid (70:29:1,v:v:v) as the extraction solvent and no clean-up method. The optimized method was then validated through determination of linearity, limits of detection (LOD), limits of quantification (LOQ), accuracy, precision and matrix effect. The LODs and LOQs in mycotoxins standards and PKC samples ranged from 0.02 to 17.5 ng g-1 and from 0.06 to 58 ng g-1, respectively. The mean recoveries of mycotoxins in PKC samples which have been added with standard solution ranged between 81-112%. The intra-day and inter-day precision values were in the range of 1.41-14.35% and 1.72-16.97%,respectively. The validated method was successfully applied on 25 PKC samples obtained from feed industries. The study found that all of the samples were contaminated with at least 7 out of 11 mycotoxins being studied. A total 96% of the samples exceeded the maximum regulatory limits of 5 and 100 ng g-1 for aflatoxin B1 and zearalenone, respectively. In conclusion, the newly developed and optimized LCMS/MS method is sensitive, efficient and reliable for the simultaneous determination of multi-mycotoxins, which can be ideal to be used for routine analysis in laboratories.